2010
DOI: 10.1248/bpb.33.714
|View full text |Cite
|
Sign up to set email alerts
|

Allergy-Preventive Effects of the Flowers of Impatiens textori

Abstract: Whole plant of Impatiens textori MIQ. (Balsaminaceae) is an annual herbaceous plant that grows naturally along waterfronts in the mountains in almost every region of Japan. It has been used for detoxication and treatment of carbuncles and contusions in Chinese medicine. 1) However, there has been no report on the antiallergic effects of the flowers of I. textori. In a previous study, we demonstrated the antianaphylactic, antipruritic, and antiplatelet activating factor (PAF) activities of a 35% EtOH extract (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…It is long known that some flavonoids may act as lysozyme inhibitors [20]. Previous works also reported that plant extracts mainly composed of apigenin, luteolin and luteolin glucosides decreased allergy symptoms caused by egg-white lysozyme sensitization in rats [8]. The same anti-allergic effect was observed for Perilla frutescens water extract, and by its major component, rosmarinic acid [16].…”
Section: Discussionmentioning
confidence: 69%
“…It is long known that some flavonoids may act as lysozyme inhibitors [20]. Previous works also reported that plant extracts mainly composed of apigenin, luteolin and luteolin glucosides decreased allergy symptoms caused by egg-white lysozyme sensitization in rats [8]. The same anti-allergic effect was observed for Perilla frutescens water extract, and by its major component, rosmarinic acid [16].…”
Section: Discussionmentioning
confidence: 69%
“…This compound has been isolated from the flowers of Impatiens textori Miq. and exhibited anti-allergic property in mice (Iwaoka et al, 2010). Normally, the flavonoids found in I. balsamina are kaempferol, quercetin and myriticin.…”
Section: Concentration (Mg/l)mentioning
confidence: 99%
“…The activity used in vivo assay methods for monitoring the blood flow decrease in the tail vein microcirculation of mice subjected to sensitization with hen egg white lysozyme. The principal compounds in Impatiens textori: apigenin and luteolin 7-glucoside showed significant allergy preventive effect (Iwaoka E et al, 2010).…”
Section: Anti Allergic Activitymentioning
confidence: 99%